Literature Study: Comparison of the Effectiveness of the Stepping Stone Method and the Modified Distribution (MODI) Method for Optimizing Transportation Costs - Harahap, Lokot Muda; Ambarita, Cristin Melani Br; Cahyati, Dwi Utami; Sihotang, Maria Magdalena; Situmorang, Romulus; Silaban, Marthen Yosef (Economic: Journal Economic and Business, 2023)
The purpose of transportation is to determine optimal distribution patterns from various sources (supply) to various destinations (demand) to minimize overall production and transportation costs. This literature research is a type of descriptive qualitative research with literature review. The aim of this research is to provide an overview of the comparative effectiveness of the Stepping Stone Method and the Modified Distribution Method (MODI) for optimizing transportation costs. Based on the results of the study conducted using a case study example in the reference journal, the results show that the use of these two methods produces the same amount of results. However, the researcher provides a study that is: The Stepping Stone Method will be more effectively used if the transportation problem is small and simple, an optimal guaranteed solution is required, and sufficient time and resources are available for calculation. Meanwhile, the Modified Distribution Method will be more effective if: Large and complex transportation problems, Near-optimal solutions with time efficiency are required, and Users are not familiar with optimization methods.